An Analysis on Students’ Translation Equivalence in Translating Idiom: Penelitian - Analdi, Silvius; Bunau, Eusabinus; Suhartono, Luwandi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The aims of this study are to find out: (1) the types of equivalence translation used by students of the fifth semester of English Language Education Study Program, Tanjungpura University in the academic year of 2023/2024 in translating English idioms into Indonesian based on Newmark’s theory of translation, (2) the accuracy and the readability of their translations. This research employed a descriptive quantitative design, with data collected through a translation test. The result of the study showed that out of 200 translations produced by 20 students, 173 translations (86.5%) were classified as translation equivalence, with 74 translations (37%) categorized as semantic equivalence, and 99 translations (49.5%) as communicative translation. Furthermore, based on the categorization table, both the accuracy and readability of the students’ translations were rated as good, with average scores of 22.35 (74.5%) for accuracy and 23.9 (79.66%) for readability. These results suggest that while students moderately prioritize meaning over form, challenges remain in maintaining both accuracy and naturalness of the translation.